PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS LECTORA INSPIRE PADA MATERI KELILING DAN LUAS BANGUN DATAR SEGI EMPAT DI KELAS V SEKOLAH DASAR - Sukma Kurnia Syukra; Sahrun Nisa; Sherliyane Hendri; Masniladevi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The limited use of digital learning media creates opportunities to develop more interactive learning. The use of available technology makes learning more engaging and helps improve students’ understanding. This study is a development research that produced a learning media product based on Lectora Inspire on the topic of perimeter and area of quadrilaterals for fifth-grade elementary school students. The development model used is ADDIE. The material validation obtained 94% in the “very valid” category, media validation 88% in the “very valid” category, and language validation 90% in the “very valid” category. The practicality test results showed a teacher response of 96.6% in the “very practical” category and a student response of 95.5% in the “very practical” category. The effectiveness test results were 0.727 in the first meeting and 0.735 in the second meeting, both in the “very effective” category. Based on these findings, it is concluded that the developed Lectora Inspire-based learning media is highly feasible and recommended. Keywords: Plane Figures, Perimeter and Area, Lectora Inspire, Mathematics, Learning Media, Elementary School.